Preparing Schrödinger Cat States in a Microwave Cavity Using a Neural Network - Hector Hutin; Pavlo Bilous; Chengzhi Ye; Sepideh Abdollahi; Loris Cros; Tom Dvir; Tirth Shah; Yonatan Cohen; Audrey Bienfait; Florian Marquardt; Benjamin Huard (PRX Quantum)
Scaling up quantum computing devices requires solving ever more complex quantum control tasks. Machine learning has been proposed as a promising approach to tackle the resulting challenges. However, experimental implementations are still scarce. In this work, we demonstrate experimentally a neural-network-based preparation of Schrödinger cat states in a cavity coupled dispersively to a qubit. We show that it is possible to teach a neural network to output optimized control pulses for a whole family of quantum states. After being trained in simulations, the network takes a description of the target quantum state as input and rapidly produces the pulse shape for the experiment, without any need for time-consuming additional optimization or retraining for different states. Our experimental results demonstrate more generally how deep neural networks and transfer learning can produce efficient simultaneous solutions to a range of quantum control tasks, which will benefit not only state preparation but also parametrized quantum gates.